"FEEL IT, SHARE YOUR FEELING," AN APPLICATION FOR INDONESIANS FREE FROM STIGMA - Puspitasari, Reni; Melati, Nimsi; Febrianti, Santahana (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2024)
One of the factors that affect a person's mental health is the presence of stigma or adverse judgment. People who may often face stigma are those with HIV/AIDS (PLHIVA), COVID-19 survivors, and health workers caring for COVID-19 patients. Stigma is divided into enacted stigma and internalized stigma related to beliefs, behaviors, and actions. Overcoming stigma may be done by increasing knowledge using technology in this digital era. The researcher developed an application named "Feel It, Share Your Feeling" for the community, especially for people living with HIV/AIDS, COVID-19 survivors, and health workers caring for COVID-19 patients who are experiencing stigma. The study used a quasi-experimental method with randomized pretest-posttest designs, involving 60 respondents divided into intervention and control groups. The pre and post-intervention data were measured in both groups using The Multidimensional Measure of Internalized HIV Stigma. The data was analyzed using Wilcoxon Signed-Ranks and Mann-Whitney tests. Over a month, the intervention group showed a reduction in internal stigma, with 73.33% reporting lower stigma levels after using the Feel It, Share Your Feeling application. The Wilcoxon test results showed a computed p-value of 0.005, and the Mann-Whitney test results also indicated a p-value of 0.005. The use of the Feel It, Share Your Feeling application was found to lower internal stigma and provide accessible therapies for people living with HIV/AIDS, COVID-19 survivors, and health workers caring for COVID-19 patients. Keywords: Stigma; covid-19; HIV; nurse; mental health